2017
DOI: 10.1177/1010428317705763
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic performance of tumor markers AFP and PIVKA-II in Chinese hepatocellular carcinoma patients

Abstract: Alpha-fetoprotein is an effective biomarker as an aid in hepatocellular carcinoma detection in many countries. However, alpha-fetoprotein has its limitations, especially in early hepatocellular carcinoma diagnosis. Protein induced by vitamin K absence or antagonist-II is another biomarker that is used for hepatocellular carcinoma detection. The aim of this study is to compare the diagnostic performance of alpha-fetoprotein and protein induced by vitamin K absence or antagonist-II alone and in combination to ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 28 publications
(31 reference statements)
1
15
0
Order By: Relevance
“…A total of 144 studies were identified from the searches conducted, of which five [ 9 , 24 , 31 33 ] studies were considered suitable for inclusion in the meta-analysis, after exclusion of reviews, case reports, duplications, conference proceedings, and other unsuitable studies. All included studies were published in English.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…A total of 144 studies were identified from the searches conducted, of which five [ 9 , 24 , 31 33 ] studies were considered suitable for inclusion in the meta-analysis, after exclusion of reviews, case reports, duplications, conference proceedings, and other unsuitable studies. All included studies were published in English.…”
Section: Resultsmentioning
confidence: 99%
“…All included studies adopted a retrospective design, and this was not regarded as the representative of the patient spectrum. In addition, three [ 24 , 31 , 32 ] studies did not clearly describe the exclusion criteria applied. However, other items were effectively reported, and all six studies scored an “A.”…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“… 9 PIVKA-II has higher sensitivity and specificity values than AFP for HCC diagnosis; combining PIVKA-II with AFP increases these values even more. 10 , 11 PIVKA-II is recommended as a tumor marker for HCC surveillance by the American Association for the Study of Liver Diseases (AASLD), the European Association for the Study of Liver (EASL), and the Japan Society of Hepatology, and has been widely used in those regions. AFP is not recommended by AASLD and EASL because of its lower sensitivity and specificity values.…”
Section: Introductionmentioning
confidence: 99%